Distribusi Pneumonia Menurut Kasus Gizi Buruk dan Cakupan Imunisasi Pada Balita Di Jombang - Lia Dwi Lestari; Lucia Yovita Hendrati (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
ABSTRACT Background: The program for finding pneumonia cases as an effort to prevent and control infectious diseases in Jombang is getting better. Risk factors for pneumonia in infants include complete basic immunization (IDL) status and nutritional status in infants. Complete basic immunization coverage in Jombang has met the Ministry of Health Strategic Plan 2015-2019 target of 80%, however pneumonia cases continue to occur and have continued to increase for the past 3 years.Objectives: Observing the trend between complete basic immunization coverage and cases of malnutrition with the incidence of pneumonia in children under five in Jombang Regency during 2015, 2016, 2017 and describe the distribution of cases in the form of maps.Methods: This type of research is descriptive by describing in the form of a map. The population in this study were all children under five in Jombang. Data was taken from the Jombang health profile in 2015, 2016 and 2017. Data management uses the Health Mapper application version 4.3.0.0 with product version 4.03.Results: The trend of the incidence of pneumonia with IDL coverage in Jombang in 2015-2017 shows, an increase in pneumonia cases in infants accompanied by a decrease in IDL coverage. This incident occurred in 19.04% in Jombang, specifically in Mojoagung, Sumobito, Ploso and Plandaan. While the increase in pneumonia was accompanied by an increase in cases of malnutrition occurred in 23.8% of the districts namely Ngoro, Mojowarno, Bareng, Sumobito and Plandaan.Conclussions: During 2015, 2016 and 2017 the incidence of pneumonia tends to increase followed by a decrease in IDL coverage and an increase in cases of malnutrition.ABSTRAK Latar Belakang: Progam penemuan kasus pneumonia sebagai upaya pencegahan dan pengendalian penyakit menular di Jombang semakin membaik. Faktor risiko dari pneumonia pada balita diantaranya adalah status imunisasi dasar lengkap (IDL) dan status gizi pada balita. Cakupan IDL di Kabupaten Jombang telah memenuhi target Renstra Kementrian Kesehatan tahun 2015-2019 sebanyak 80%, namun demikian kasus pneumonia tetap terjadi serta terus mengalami peningkatan selama 3 tahun tersebut.Tujuan: Melihat kecenderungan antara cakupan IDL dan kasus gizi buruk dengan kejadian pneumonia pada balita di Kabupaten Jombang selama tahun 2015, 2016, 2017 serta menggambarkan persebarannya dalam bentuk peta.Metode: Jenis penelitian ini adalah peneltian deskriptif dengan menggambarkan dalam bentuk peta. Populasi dalam penelitian ini adalah seluruh balita di Kabupaten Jombang. Data diambil dari profil kesehatan Jombang pada 2015, 2016 dan 2017. Manajemen data menggunakan aplikasi Health Mapper versi 4.3.0.0 dengan versi produk 4.03.Hasil: Kecenderungan kejadian pneumonia dengan cakupan IDL di Jombang pada tahun 2015-2017 menunjukkan terjadi peningkatan kasus pneumonia pada balita disertai dengan penurunan cakupan IDL. Kejadian ini terjadi di 19,04% kecamatan di Jombang tepatnya kecamatan Mojoagung, Sumobito, Ploso dan Plandaan. Sedangkan peningkatan pneumonia disertai dengan peningkatan kasus gizi buruk terjadi di 23,8% kecamatan yaitu Kecamatan Ngoro, Mojowarno, Bareng, Sumobito dan Plandaan. Kesimpulan: Selama tahun 2015, 2016 dan 2017 kejadian pneumonia cenderung mengalami peningkatan yang diikuti dengan penurunan cakupan IDL serta peningkatan kasus gizi buruk.